(untitled) (Journal of Medicine, 2022)
Background: Lung cancer is the most common fatal neoplastic disease and the leading cause of cancerrelated deaths worldwide. In Bangladesh, lung cancer has been on the rise, possibly due to an increase in smoking and air pollution. So, it is essential to understand the natural history of this disease. Aim: This study aimed to find out the correlation between Clinico-radiological profiles with histopathological patterns of lung cancer in Bangladesh. Material and Methods: A total of 100 confirmed cases of lung cancer were included in this crosssectional observational study between January 1, 2021, to December 31, 2021. The complete sociodemographic characteristics, smoking status, previous history of COPD, details of radiological imaging findings, pathological characteristics of the tumor, and the performance status of patients were recorded in this study. Data were entered and analyzed using SPSS software. Results: A total of 100 (86 male, and 14 female) confirmed lung cancer patients were included in our study with a mean ± SD age of 59.57±10.41 years. Cough (87%), breathlessness (61%), and chest pain (58%) were the most common symptom and mass lesions (83%) followed by collapse (8%) was the most common radiological presentation. Among the histopathological types adenocarcinoma (48%) was the most common type followed by squamous cell carcinoma (35%). Correlation showed that mass lesion was the most common radiological finding in both adenocarcinoma and squamous cell carcinoma. ECOG performance status 2, and status 3 were about 36% and 35% respectively. Multivariate logistic regression analysis shows male gender with COPD independently had a 1.681-fold risk of developing lung cancer. Conclusion: The Clinico-histopathological pattern of lung cancer has changed recently. The incidence of adenocarcinoma is increasing, and becoming the most common cause in both smokers and non-smokers. J MEDICINE 2022; 23: 126-131